Snow sisters The crystal rose - Foss,Astrid (London: Nosy Crow Ltd, 2018)
The evil Shadow Witch will do anything to stop the Snow Sisters from reaching the Everchanging Lights before her... On their second quest, the girls face a dark, icy journey to find the crystal rose and the blue Everchanging Light. Will their magic be strong enough to overcome the Great Glacier and all the dangers hidden there? Have you read the Snow Sisters' first adventure, 'The Silver Secret'? Look out for the Snow Sisters' next adventures, 'The Frozen Rainbow' and 'The Enchanted Waterfall'!